A new empirical model for shear strength of reinforced concrete beam-column connections - Tran, T.; Hadi, M.; Pham, Thong (2014)
A new empirical model to estimate the joint shear strength of both exterior and interior beam-column connections is proposed. In the model, four parameters that have the most influence on joint shear strength are considered. Among these four, a new parameter is introduced to consider the bond condition and the possibility of beam bars transferring joint shear force into the columns. Consideration of this parameter in the model significantly improves the accuracy of the predicted joint shear strength. To calibrate the model, a large database of 98 reinforced concrete (RC) exterior and 73 RC interior beam-column connections displaying joint failure mode was compiled from the literature. A parametric study was also carried out to evaluate the dependence of the predicted to tested joint shear strength ratio on the four influence parameters using the database. The proposed model showed superior performance over existing models. Moreover, comparisons of the predicted joint shear strength with experimental results and with four existing models showed the accuracy of the proposed model.